2002
DOI: 10.1021/jp026180b
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steric Stabilization on the Arrested Growth of Silver Nanocrystals in Supercritical Carbon Dioxide

Abstract: Perfluorodecanethiol-stabilized silver (Ag) nanocrystals were synthesized in supercritical (sc)-CO2 through arrested precipitation, by reducing silver acetylacetonate (Ag(acac)) with hydrogen in the presence of fluorinated thiol. The CO2 density used during synthesis controls the particle size and polydispersity. At high solvent densities, (P > 250 bar, T = 80 °C), the ligands provide a strong steric barrier that maintains small particles with a 20 Å diameter. At lower solvent densities (P < 250 bar, T = 80 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 43 publications
(86 reference statements)
0
118
0
Order By: Relevance
“…[23] A recent discussion on the values of Hamaker constants of iron oxide NPs can be found in a paper by Faure. [24] It can be calculated as: …”
Section: Van Der Waals Forcesmentioning
confidence: 99%
“…[23] A recent discussion on the values of Hamaker constants of iron oxide NPs can be found in a paper by Faure. [24] It can be calculated as: …”
Section: Van Der Waals Forcesmentioning
confidence: 99%
“…Supercritical CO 2 also proved to be a good solvent for fluorous nanoparticles synthesis by using suitable organometallic precursors and hydrogen as reducing agent [21,22].…”
Section: "Perfluorinated" Gold Nanoparticlesmentioning
confidence: 99%
“…The van der Waals attractive force 27 , Φ vdW , between two particles increases with an increase in particle radius R or with a decrease in center to center separation distance between the particles d. Φ vdW is directly proportional to the Hamaker constant, A 131 . A 131 is a proportionality factor that accounts for the interaction between two nanoparticles of the same material (component 1) across a solvent (component 3) and depends on A 11 and A 33 , where A 11 is a constant value for metallic nanoparticles with A 11 = 2.185 eV for silver 26 and A 33 for the solvent is calculated by an equation of state based on Lifshitz theory 28 . A 33 depends on the refractive index n, and dielectric constant ε of the solvent as given in equation (4) components (in this case, CO 2 and hexane), so a new mathematical expression was developed to calculate the Hamaker constant where 3' represents one of the solvent components (in this case CO 2 ) and 3" represents the other solvent component (e.g.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…There is experimental evidence that thiol tails on a metal surface are in the extended mode. For example, using IR spectroscopic and ellipsometric data, Porter et al 39 have shown that thiol tails with hydrocarbon group (-CH 2 ) greater than 9 assemble on gold surfaces in a densely packed manner with fully extended alkyl chains tilted from the surface normal by [20][21][22][23][24][25][26][27][28][29][30] o . This suggests that the Condensed Phase Model may not be the correct phenomenological model for our experimental system.…”
Section: Condensed/collapsed Phase Model (Cpm)mentioning
confidence: 99%